Genomic analysis of human respiratory adenovirus transmission (Colombia Medica, 1992)
From 84 respiratory and fecal samples, 3 pairs of adenovirus were recovered. Using a model of closed contact restriction analyses (RA) of the 3 pairs of adenovirus were performed. Upon the RA criterion, one pair was identified as adenovirus serotype 2 Ton 99, the second as an adenovirus serotype 6 (A6.1 variant), and the last one was characterized as Ad3GB strain. The comparison of restriction patterns of isolated pairs showed full coomigration in each case. Evidence is given that RA is a powerful tool in studying respiratory adenovirus transmission mechanisms in closed-contact children.